A novel adaptive state-of-charge balancing control scheme for cascaded H-bridge multilevel converter based battery storage systems. (April 2023) - Eroğlu, Fatih; Kurtoğlu, Mehmet; Eren, Ahmet; Vural, Ahmet Mete
Abstract: Variations in state-of-charges (SOCs) of batteries in a cascaded H-bridge multilevel converter (CHB-MLC) based battery storage system (BSS) could lead to undesired efficiency and performance drops, even failure of the whole system. Hence, SOC balancing is crucial for BSSs. Avoiding over-modulation region, ensuring zero common-mode voltage and reaching balanced SOC condition as quickly as possible are the key points to consider while performing SOC balancing. In this paper, a gain-scheduling based adaptive SOC balancing method is proposed for single-phase CHB-MLC based BSSs. In the proposed method, gains of the proportional controllers are updated at each sampling time based on the mathematical relationship between instantaneous SOCs and voltage reference of the CHB-MLC. Performance of the proposed method is validated through a Monte Carlo simulation based numerical analysis and experimental studies on a single-phase three-module CHB-MLC based BSS. Results reveal that the proposed method achieves SOC balancing at least two times faster than the traditional constant gain methods while avoiding over-modulation region and having zero common-mode voltage. Highlights: Over-modulation region is avoided for all instantaneous SOC conditions. Zero CM voltage throughout the SOC balancing operation is ensured. SOC balancing speed is increased at least two times compared to traditional methods. Battery capacity losses are reduced at least 40 % compared to traditional methods. SOC balancing speed and battery capacity losses are verified by Monte Carlo simulation.